Analisis Kadar Vitamin B1 dalam Kacang Panjang (Vigna sinensis L.) Menggunakan Spektrofotometri Ultraviolet-Visible - Armin, Fithriani; Andayani, Regina; Hilson, Denny; Azzaky, Azzaky (Jurnal Geografi, Lingkungan dan Kesehatan, 2023)
A Research of vitamin B1 in long beans (Vigna sinensis L.) analyzed using ultraviolet-visible (uv-vis) spectrophotometry has been carried out at a wavelength of 435.6 nm. Vitamin B1 reacted with bromthymol blue to form a yellow ion-associated complex in an ammonia-ammonium chloride as a buffer solution pH 7.6 which could be observed with a polyvinyl alcohol solubilizing agent. Long beans were boiled in water for 5, 10 and 15 minutes at 100oC. Vitamin B1 in long beans (Vigna sinensis L.) without boiling 0.0981 % ± 0.00021, boiling 5, 10 and 15 minutes were 0.0935 % ± 0.00015; 0.0834 % ± 0.00010 and 0.0743 % ± 0.00010 and the vitamin B1 in the long bean boiled water at 5, 10 and 15 minutes boiling were 0.00102 % ± 0.000004; 0.00110 % and 0.00117 % ± 0.00001. It’s can be concluded that boiling long beans (Vigna sinensis L.) can cause a decrease in vitamin B1 which decreases with increasing boiling time and vitamin B1 in the cooking water increase due to the nature of vitamin B1 which is easily soluble in water